Carbon and Nitrogen Isotopic Similarity Between the Endangered Darwin’S Fox (Lycalopex Fulvipes) and Sympatric Free-Ranging Dogs in Chiloé Island, Chile - Moreira-Arce, D (Taylor and Francis Ltd., 2022)
Darwin’s fox is an opportunistic omnivorous predator native to Chile classified as endangered by the IUCN Red List. Habitat use by Darwin’s foxes can be negatively affected by the presence of free-ranging dogs that range freely across native and non-native habitats and can be a source of fox mortality. The objective of this study was to analyze the isotopic similarity of Darwin’s fox and sympatric free-ranging dogs in Chiloé Island to determine the impact of anthropogenic environmental alterations on wild predators. We use hair samples to characterise and compare their δ 13C and δ 15N values and to evaluate isotopic similarity and isotope niches overlap. A generalised linear model was used to associate the isotope value with landscape variables (forest cover and vegetation type) and distance to the nearest house. We found no significant differences in δ 13C or δ 15N values between foxes and dogs, and a marginally significant isotope niche overlap (59.4 %). None of the selected variables at landscape and site scale were related to isotope values. Although our study is not a probe of direct contact between foxes and free-ranging dogs, the high isotopic similarity highlights the risk of pathogen spillover from free-ranging dogs to Darwin’s foxes. © 2022 Informa UK Limited, trading as Taylor & Francis Group.